Influence of Ni ion site occupancy on laser induced third harmonic generation (THG) studies in Li2SO4–MgO–P2O5 amorphous system. Issue 18 (15th September 2021) - Sekhar, A. Venkata; Sesha Reddy, A. Siva; Kityk, A.V.; Jedryka, J.; Rakus, P.; Wojciechowski, A.; Kumar, V. Ravi; Veeraiah, N.
Abstract: Glasses of the composition Li2 SO4 –MgO–P2 O5 mixed with varied contents (0.2–1.0 mol%) of nickel oxide were synthesized. Various spectroscopic investigations have indicated gradual growing proportions of O h Ni 2+ ions in the host glass. IR spectral results, in particular, have clearly demonstrated an increased degree of structural disorder of the glass nerwork with increased content of NiO. The intensity of third harmonic generation (THG) component of probing beam viz., Nd:YAG laser (λ = 1064 nm and power density J = 0–200 J/m 2 ) induced due to the interaction of inherent dipoles with the incident laser beam, exhibited an increasing trend with increase of nickel oxide concentration up to 0.8 mol%. Analysis of the results of these studies indicated that Li2 SO4 –MgO–P2 O5 glass samples doped with optimal content of NiO ( 0.8 mol%) are more favorable for achieving intense THG beam with low phonon losses. Hence, such glasses may be considered as useful for optoelectronic devices. On the other hand, the samples doped with NiO content greater than 0.8 mol%, the Ni 2+ ions seemed to prefer (revealed by optical absorption and IR spectroscopy studies) tetrahedral occupancy in the glass matrix and enhance the degree of the polymerization of the glass matrix; such increased order of polymerization of the glass matrix appears to be a hindrance for accomplishing higher intensity of THG signal due to large phonon losses. These results were found to be in concurrence with the inferences from other studies that include electrical properties, positron annihilation lifetime (PAL) spectroscopy and mechanical properties.